Modeling FoMO as a psychological mediator in relationship between phubbing and social media addiction among university students: A PLS-SEM - Syarifah Ivonesti; Nina Zakiah; Syarifah Hidayah Fatriah (Jurnal Konseling dan Pendidikan, 2026)
This study investigates the mediating role of Fear of Missing Out (FoMO) in the relationship among phubbing and social media addiction among undergraduate students. Excessive social media use and problematic smartphone behavior have increasingly been associated with psychological distress and addictive digital behaviors among young adults. Using a quantitative explanatory research design, data were collected from 291 undergraduate students through convenience sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement instruments were adapted from previously validated scales assessing phubbing, FoMO, and social media addiction. The findings revealed that phubbing had a significant positive effect on FoMO (β = 0.334, p < 0.001) and social media addiction (β = 0.359, p < 0.001). Furthermore, FoMO significantly predicted social media addiction (β = 0.671, p < 0.001). Mediation analysis demonstrated that FoMO significantly mediated the relationship between phubbing and social media addiction (β = 0.224, t = 4.98, p < 0.001), indicating a partial mediation effect. The structural model showed moderate explanatory power, with R² values of 0.540 for FoMO and 0.573 for social media addiction. These results recommed that psychological factors, particularly FoMO, provude to explaining how phubbing behavior is associated with dificult social media use among university students. This study contributes to the increasing theory on digital behavior by integrating behavioral and cognitive-emotional factors within a single structural framework.